2000
DOI: 10.1007/s002030000216
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerant phenol-degrading microorganisms isolated from Amazonian soil samples

Abstract: Two phenol-degrading microorganisms were isolated from Amazonian rain forest soil samples after enrichment in the presence of phenol and a high salt concentration. The yeast Candida tropicalis and the bacterium Alcaligenes faecoalis were identified using several techniques, including staining, morphological observation and biochemical tests, fatty acid profiles and 16S/18S rRNA sequencing. Both isolates, A. faecalis and C. tropicalis, were used in phenol degradation assays, with Rhodococcus erythropolis as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(9 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Similar results were found in Brazil by Bastos et al (2000) in virgin forest soil and a second location adjacent to the forest area subjected to slashand-burning activities. The salt-tolerant microorganisms isolated in the present study could become a promising option for their use in bioremediation processes for industrial effluents or contaminated soils based on their co-adaptation.…”
Section: Acknowledgementssupporting
confidence: 87%
“…Similar results were found in Brazil by Bastos et al (2000) in virgin forest soil and a second location adjacent to the forest area subjected to slashand-burning activities. The salt-tolerant microorganisms isolated in the present study could become a promising option for their use in bioremediation processes for industrial effluents or contaminated soils based on their co-adaptation.…”
Section: Acknowledgementssupporting
confidence: 87%
“…Rhodotorula glutinis [50]), Betaproteobacteria (e.g. Alcaligenes faecalis [52] and Comamonas [51]) and Sordariomycetes (e.g. Phomopsis liquidambari [53] and Trichoderma harzianum [29]) could degrade phenols.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, C. tropicalis is able to grow in culture medium with more than 10–15% sodium chloride and has been isolated from the hypersaline environment for the first time from Dead Sea samples (Butinar et al, 2005 ). Bastos et al ( 2000 ) reported the isolation of this yeast from a sample of Amazonian forest enriched with high salt concentration.…”
Section: Tropicalis Osmotic Stress Response and Biotechnomentioning
confidence: 99%